(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The study aimed to identify the degree of acquisition of faculty members’ technological, educational and content knowledge according to the framework (TPACK) at the College of Education at University of Hail. The study used the quantitative method, and the questionnaire was a survey to achieve its goal. The population of study were 84 faculty members and 326 students. The results of the study revealed that there is a high degree of faculty members’ (TPACK) from their point of view with a mean of (4.177). The results also showed that there was a correlation between the responses of the faculty members and the responses of the students for the faculty members’ (TPACK) seven components. The study included a number of recommendations and suggestions.